Impact of Qur’anic Moral Excellence on the Lives of Muslim Society: An Exposition - Attahir Shehu Mainiyo; Muhammad Maga Sule (Demak Universal Journal of Islam and Sharia, 2023)
The Glorious Qur’an, as the central religious text of Islam addresses various aspects of human life and provides guidance for personal and societal development. It also outlines the moral excellence of individuals and communities, focusing on spiritual, moral, and social dimensions. The Glorious Qur’an recognizes the challenges faced by humanity and encourages efforts towards global human development. It, however, harps on the cultivation of moral virtues and ethical behaviour thereby promoting justice, honesty, compassion, humility, patience, and generosity. Principles of social justice and equality and the calls for the eradication of discrimination based on race, gender, as well as social status, have aptly been captured in a plethora of Qur’anic verses. It is thus in line with this backdrop that this article intends to assess the impact of Qur’anic moral excellence on the lives of Muslim society towards human moral development. However, to achieve the objectives of the research, the article attempts to answer some basic questions. How did the Qur’an emphasize the need for social cohesion and working together to address societal challenges? What efforts are necessary for enhancing human moral development? What are the contributing factors toward promoting justice, peace, and well-being of human society? What are the principles the Qur’an provides for effective navigation toward a better future for all? The article adopts an analytical methodology.